Musical Instruments in Samāʿ Literature: al-Udfuwī’s Kitāb al-Imtāʿ bi-aḥkām as-samāʿ - Klein, Yaron (Oriens, 2023)
Samāʿ literature reveals a tension in premodern Islamicate societies. While musical practices were ubiquitous and practiced in many contexts, Islamic legal tradition regarded them with suspicion. Musical instruments occupied a central place in these discussions, perhaps, because as physical objects associated with what is otherwise in the non-tangible domain of sound they were seen as the quintessential manifestation of music. Udfuwī’s Imtāʿ is one of the most comprehensive works in the genre, and its chapter on instruments is unique in both the length and place it ascribes to percussion instruments. Udfuwī argues for their permissibility and stresses their social importance throughout history.